Guiding vacuum-assisted biopsy in prone position: digital breast tomosynthesis vs stereotactic. Issue 4 (August 2022) - Scaperrotta, Gianfranco P.; Boffelli, Giulia; Depretto, Catherine; Di Leo, Giovanni; Liguori, Alessandro; Monaco, Cristian Giuseppe; Borelli, Anna; Ferranti, Claudio
Purpose: To compare the performance of prone digital breast tomosynthesis (DBT)–vacuum-assisted biopsy (VAB) with prone stereotactic-guided VAB (sVAB), focusing on time of procedure, number of expositions, average glandular dose, and complications. Methods: The institutional review board approved this retrospective study and informed consent was waived. From July 2015 to January 2017, 306 patients with 306 suspicious mammographic findings (BI-RADS ⩾4) underwent mammography-guided biopsy, prone sVAB, or prone DBT-VAB. Student t test, chi-square, and multivariate regression statistics were used. Results: During the study period, 155 prone sVAB procedures in 155 patients (mean age, 56 years; age range, 39–84 years) and 151 DBT-VABs in 151 patients (mean age, 57 years; age range, 33–84 years) were performed. Mean procedure time was shorter with DBT-VAB versus sVAB (14.5 versus 17.4 minutes, respectively; p < 0.001), and fewer images were acquired with DBT-VAB versus sVAB (8 vs 11, respectively; p < 0.001); the average glandular dose was significantly lower in DBT-VAB versus sVAB (11.8 mGy versus 18 mGy, respectively; p < 0.001). There were no differences in the distribution of histologic results ( p = 0.74) or breast density ( p = 0.09) between the two groups. No major complications were observed in either group. Conclusion: Performance of prone DBT-VAB was superior to prone sVAB because it allowed a faster procedure with fewer radiologic expositions and lower radiation dose.